Curricular diversification (Journal of Parents and Teachers, 2025)
The article addresses Attention to Diversity, where Curricular Diversification Programs are implemented to meet the needs of all students, regardless of their situation and cognitive development. To achieve this, programs are carried out for these students with a series of objectives that must be addressed in the 3rd and 4th grades of Primary Education.
Keywords: students; diversity; attention; needs